Extracorporeal Liver Support in Liver Failure: A Comprehensive Review of MARS, SPAD, Prometheus, ADVOS, and Bioartificial Systems - Meta Restu Synthana; Akhmad Yun Jufan; Calcarina Fitriani Retno Wisudarti; Fiandila Elvana Deviatika (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2025)
Background : Acute and chronic liver failure are life-threatening conditions often requiring liver transplantation as definitive therapy. To delay or substitute the need for transplantation, various extracorporeal liver support systems have been developed. This article aims to review current artificial and bioartificial liver support systems including the Molecular Adsorbent Recirculating System (MARS), Single Pass Albumin Dialysis (SPAD), Prometheus, ADVanced Organ Support (ADVOS), and Bioartificial Liver (BAL) devices.Discussion : MARS and SPAD utilize albumin-based dialysis to remove protein-bound and water-soluble toxins. Prometheus applies a fractionated plasma separation and adsorption approach, while ADVOS enables individualized acid-base correction. Bioartificial liver systems integrate hepatocyte bioreactors with plasma dialysis to provide more physiological metabolic support. While these systems show promise in improving clinical outcomes, long-term survival benefit remains under investigation.Conclusion : Extracorporeal liver support systems offer essential bridging and supportive therapies for patients with liver failure. Selection should be tailored to patient condition, therapeutic goals, and technology availability.